GMTR ANALYSIS CREATE OPTIMAL ECONOMIC GROWTH - Yossinomita Yossinomita; Febby Nanda Utami; Vivi Usmayanti; Effiyaldi Effiyaldi; Yuni Zuliawati; Ikrima Khairunnisa (Jurnal Akuntansi dan Pajak, 2023)
Laffer curve theory is applied in this study using an endogenous growth model supported by production or utility-related taxes. Estimated tax rates that maximize economic growth can be determined by modeling the relationship between taxes and economic growth. The maximum level of this model is known as the growth maximizing tax ratio (GMTR). The results of Ordinary Least Square (OLS) based on the magnitude of the regression coefficient show that the GMTR, which creates optimal Indonesian economic growth, is 12.00%.